PercepFiguras: a computerized visual stimulation program to assess, behaviorally and electrophysiologically, the multistable perception - Ortiz-Cruz, E. E.; Rodríguez-Camacho, H.; Rodríguez-Camacho, M. A.; Bernal-Hernández, J. (Revista Mexicana de Ingenieria Biomedica, 2018)
In the study of visual perception, the use of computerized commercial programs for the presentation of stimuli, usually configured to admit a response for each stimulus presented, is common. However, the study of multistable perception requires the presentation of a stimulus that remains unchanged, although the perception of it can vary in two or more configurations during its observation, which demands that the program admit responses for each change in perception of the same stimulus. PercepFiguras is a system developed with C++ programming language that allows: a) present images and receive multiple responses to the same stimulus, b) synchronize the responses with an electroencephalographic recording system by sending TTL pulses, c) generate a behavioral file, d) generate a file with the total responses and averages of the latencies for each type of figure. In the pilot study with a task of continuous presentation of an ambiguous figure to alternating with two variants of less ambiguity, we observe grea-ter frequency of perceptual and less perceptual stability to the ambiguous figure with respect to the less ambiguous figures, which proves the usefulness of the program.